Cafe Pietzkendorf, Bes. Bruno Nipkow, Danzig-Pietzkendorf (Paul Lukowski. Postkartenverlag, 1914)
Przedstawia kawiarnię należącą do Bruno Nipkowa w Pieckach (Pietzkendorf) pod Gdańskiem obecnie Piecki - Migowo, ok. 1917 r.